Generating Secure Key for VoIP Network by Fusion of Irises - Bhuvaneshwari, S; Arul, P (International Journal of Computer Sciences and Engineering, 2025)
Over the year several new technologies and applications has being developed to deploy and reap the benefits of the Internet, Voice over Internet Protocol (VoIP) is one of those technologies. VoIP converts the voice signal from your telephone into a digital signal that travels over the Internet. One particular juicy offer that the VoIP provides is its cheapness and the ability to use an existing Internet connection/access to make calls. VoIP has come with both its advantages and challenges which make it yet another issue to worry about. The chief problem is to protect our data in a unique way that could only be worked upon by encrypting the voice data which run over the open network. Enforcement of using encryption is to provide confidentiality in communication channel. Using biometric we can generate an exclusive key that will be unique for each and every individual. Here we propose to make a contribution of the sender’s iris and database iris biometrics to have a secured VoIP communication. After fusing these two irises, the key will be generated. The key will be used for encrypting our data in VoIP. Thus the proposed method will provide secured VoIP communication and billions of unique keys can be generated, making VoIP technology hard for an attacker to guess the key . This key act as a symmetric key for both encryption and decryption. This proposed system is composed following modules 1) Feature extraction of Iris 2) Cryptographic key generation. 3) Fusion of irises